POST HARVEST APPLICATION OF SALICYLIC ACID ENHANCED SHELF LIFE AND MAINTAINED QUALITY OF BANANA CV. ‘GRAND NAINE’ AT AMBIENT STORAGE - MANDAL, D; NAUTIYAL, B.P; HAZARIKA, T.K (The Bioscan, 2016)
Six concentrations of Salicylic Acid (SA: 0.25, 0.5, 1.0, 1.5, 2.0 and 4.0 mM) along with control (water dipped) were tested on shelf life and quality of banana fruits stored at 23±20 C and 70±5% relative humidity. Eight days after storage (DAS), fruits treated with SA at 4.0 mM showed reasonably less skin colour development (average score: 4.3) than control (average score: 7.0). Moreover, TSS (13.82°Brix), titrable acidity (0.22%, TSS:acid ratio (62.82), total sugar (13.42%) content was found low with high ascorbic acid level (11.53 mg 100g-1) which signified that fruits had delayed ripening under this treatment. Fruit decay (5.62%) and weight loss (11.85%) was also remained low for SA (4.0mM) treated fruits and thus increased the shelf life up to six days more than control. However, SA at 2.0 mM had also caused high shelf life (13.05 days) with low fruit decay (8.85%). Study revealed that SA at 2.0-4.0 mM may be effective post-harvest treatment for extending shelf life and maintaining fruit physico-chemical qualities at ambient condition.